Food safety in Uganda's livestock value chains - Roesel, Kristina (International Livestock Research Institute, 2016)
Kristina Roesel, coordinator of the Safe Food, Fair Food project which is led by ILRI in Uganda, explains how research is improving food safety in livestock value chains in the country.